Impaired pulmonary function after treatment for tuberculosis: the end of the disease? - Mikhail Ivanovich Chushkin; Oleg Nikolayevich Ots (Jornal Brasileiro de Pneumologia)
ABSTRACT Objective: To evaluate the prevalence of pulmonary function abnormalities and to investigate the factors affecting lung function in patients treated for pulmonary tuberculosis. Methods: A total of 214 consecutive patients (132 men and 82 women; 20-82 years of age), treated for pulmonary tuberculosis and followed at a local dispensary, underwent spirometry and plethysmography at least one year after treatment. Results: Pulmonary impairment was present in 102 (47.7%) of the 214 patients evaluated. The most common functional alteration was obstructive lung disease (seen in 34.6%). Of the 214 patients, 60 (28.0%) showed reduced pulmonary function (FEV1 below the lower limit of normal). Risk factors for reduced pulmonary function were having had culture-positive pulmonary tuberculosis in the past, being over 50 years of age, having recurrent tuberculosis, and having a lower level of education. Conclusions: Nearly half of all tuberculosis patients evolve to impaired pulmonary function. That underscores the need for pulmonary function testing after the end of treatment.